Effect of plant extracts on the pepper weevil (Anthonomous eugenii Cano): Preliminary Results. - Palma, Rosa Magdalena (Agronomía Mesoamericana, 2016)
This research effort was developed at the campus of the School of Agronomical Science, from May, 1995 to February 1996, with the objective of finding alternative solutions for desirable ecological control of the A. eugenii. The experiment consisted on the evaluation of 35 plant species, in in vitro laboratory conditions , and from which aqueous extracts were prepared with a ratio of 2.5 g of plant matter and 20 mL of water (To of 800 C) and applied to leaf discs of the sweet pepper plant (leaf discs had a diameter of 1.7 cm). The discs were used to feed the pepper weevil, in order to compare the effects on their behavior (consumption of the leaf discs and mortality rates). The treatments were distributed using a Complety Random Design with five replications. From the whole set of plant extracts, five promissory species were identifield : “mamey” seed, paradise plant, “madrecacao”, Balsamic Bark, and the leaves of “palo hediondo”. The effects of those species were notorious, since the consumption levels of the leaves varied between 0 and 40 mm2, with mortality rates from 20 to 70%. The control with plain water and other plant species showed from 60 to 135 mm2 of leaf consumption and a mortality rate from 0 to 30%.